Alternative Measures for the Global Financial Cycle: Do They Make a Difference? - Xin Tian; Jan Jacobs; Jakob de Haan (Center for Economic Studies and ifo Institute (CESifo), 2022)
We construct several measures for the global financial cycle using dynamic factor models and data for 25 advanced and emerging countries over 1980-2019. Our results suggest that global cycles in asset prices and capital flows are highly similar and synchronized, especially during crisis episodes. Our measures for asset-specific global cycles suggest that cycles in credit and house prices are less volatile and have a longer duration than cycles in equity and bond prices. Finally, we find significant co-movement of our global financial cycle measures and two measures as suggested in the literature that are based on top-down and bottom-up approaches.
Keywords: E44; F32; F36; 330; global financial cycle; national financial cycle; dynamic factor analysis; capital flows; asset prices